Overview on the spatial-temporal characteristics of the ozone formation regime in China - Lu, Haoxian; Lyu, Xiaopu; Cheng, Hairong; Ling, Zhenhao; Guo, Hai (Environmental science--processes & impacts, 2019)
Ozone (O 3 ), a main component in photochemical smog, is a secondary pollutant formed through complex photochemical reactions involving nitrogen oxides (NO x ) and volatile organic compounds (VOCs). In the past few decades, with the rapid economic development, industrialization and urbanization, the mixing ratio of O 3 has increased substantially in China. O 3 non-attainment days have been frequently observed. Despite great efforts made in the past few years, it is still difficult to alleviate O 3 pollution in China, due to its non-linear relationship with the precursors. In view of the severe situation in China, this study presents a comprehensive review on the spatial-temporal variations of the relationship between O 3 and its precursors ( i.e. O 3 formation regime), built upon the previous reviews of the spatial-temporal variations of O 3 and its precursor levels. Valuable findings from previous studies are laid out for a better understanding of O 3 pollution, followed by implications for the control of O 3 pollution. This literature review indicates that O 3 formation in most areas of the North China Plain (NCP), Yangtze River Delta (YRD) and Pearl River Delta (PRD) regions is in a VOC-limited regime during the high-O 3 seasons due to dramatic emissions from human activities in cities. Outside these metropolitan areas, a NO x -limited regime dominates rural/remote areas. From summer to winter, the O 3 formation regime over China shows a tendency to shift to a VOC-limited regime. Furthermore, O 3 formation in China shifted toward increasing sensitivity to VOC emissions before the 12 th Five-Year-Plan. However, after the 12 th Five-Year-Plan, successful reduction of NO x slowed down this trend. Further effective control of VOCs is expected to achieve sustained O 3 attainment in the future. To timely solve the current O 3 pollution problem, precise control of O 3 precursors is proposed, together with the joint prevention and control of regional air pollution. Ozone (O 3 ), a main component in photochemical smog, is a secondary pollutant formed through complex photochemical reactions involving nitrogen oxides (NO x ) and volatile organic compounds (VOCs).